1994
DOI: 10.1038/367731a0
|View full text |Cite
|
Sign up to set email alerts
|

The 'blue-on' opponent pathway in primate retina originates from a distinct bistratified ganglion cell type

Abstract: Colour vision in humans and Old World monkeys begins with the differential activation of three types of cone photoreceptor which are maximally sensitive to short (S), medium (M) and long (L) wavelengths. Signals from the three cone types are relayed to the retinal ganglion cells via cone-specific bipolar cell types. Colour-coding ganglion cells fall into two major physiological classes: the red-green opponent cells, which receive antagonistic input from M- and L-sensitive cones, and the blue-yellow opponent ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
495
0
20

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 681 publications
(531 citation statements)
references
References 26 publications
16
495
0
20
Order By: Relevance
“…This fraction is measured to be 4.4 Ϯ 4.1%, based on the peak of the S-cone time filter response relative to the peak of the S-cone plus (L ϩ M)-cone response, and including an estimated cross talk of 0 Ϯ 4% between the S and (L ϩ M) cone-isolating stimuli. For comparison, the corresponding S-cone fraction measured for S-ON/(L ϩ M)-OFF cells [most likely small bistratified blue/yellow color opponent cells (Dacey and Lee, 1994)] in the same preparation is 48.4 Ϯ 16.6%, indicating that the S-cones were functioning normally (data not shown). (This insignificant S-cone input to upsilon cells, measured in the presence of simultaneously recorded S-ON/(L ϩ M)-OFF cells, was also observed in several preparations that contained only a few upsilon cells and therefore were not included in this paper.)…”
Section: Color Response Properties: S-cone Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fraction is measured to be 4.4 Ϯ 4.1%, based on the peak of the S-cone time filter response relative to the peak of the S-cone plus (L ϩ M)-cone response, and including an estimated cross talk of 0 Ϯ 4% between the S and (L ϩ M) cone-isolating stimuli. For comparison, the corresponding S-cone fraction measured for S-ON/(L ϩ M)-OFF cells [most likely small bistratified blue/yellow color opponent cells (Dacey and Lee, 1994)] in the same preparation is 48.4 Ϯ 16.6%, indicating that the S-cones were functioning normally (data not shown). (This insignificant S-cone input to upsilon cells, measured in the presence of simultaneously recorded S-ON/(L ϩ M)-OFF cells, was also observed in several preparations that contained only a few upsilon cells and therefore were not included in this paper.)…”
Section: Color Response Properties: S-cone Inputsmentioning
confidence: 99%
“…Although decades of work have been devoted to the study of primate retinal architecture, fewer than one-half of the 22 or more anatomically identified types of retinal ganglion cells (RGCs) (Rodieck and Watanabe, 1993;Dacey et al, , 2005Dacey, 2004;Yamada et al, 2005) have been characterized physiologically, namely the ON and OFF midget and parasol cells (Dacey, 1999;Chichilnisky and Kalmar, 2002), the small bistratified cells (Dacey and Lee, 1994;Chichilnisky and Baylor, 1999), the recently discovered giant sparse (melanopsin-expressing) cells (Dacey et al, , 2005Dacey, 2004), and, to some extent, the large bistratified cells and the cells of type "sparse" Dacey, 2004). One of the possible reasons for this discrepancy is that the morphological RGC types awaiting physiological characterization constitute only a small fraction of all the primate ganglion cells (1-4%) [see Dacey (2004), their table 20.1].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that this effect was also accompanied by a perceptual melting of the BY elements, in which the elements appear ill-defined and "melt" into the background. We hypothesized that the larger occupancy radius, perceptual melting effect, and density bias of the BY signal point to spatial processing differences among the postreceptoral mechanisms, which may include differences in their spatial filters, the sparseness of their spatial sampling, and differences in intracortical connectivity (Curcio et al, 1991;Dacey & Lee, 1994; Calkins , 1998). When comparing with the present experiment, it is also noteworthy that the critical separation for contour integration is about 3.5 times the occupancy diameter for the Ach mechanism, and only 1.5 times for the BY mechanism (Table 1).…”
mentioning
confidence: 99%
“…It was initially thought that SWAP targets parvocellular blue-yellow retinal ganglion cells projecting to the parvocellular layers of the lateral geniculate nucleus, i.e., the parvocellular (P) pathway. However, it was later shown that blue-yellow cells are in fact small bistratified ganglion cells, which project their axons to the koniocellular layers of the lateral geniculate nucleus (Dacey and Lee, 1994;Sample et al, 2006). Several studies have compared the ability of SAP, SWAP, and/or FDT to detect glaucoma but have shown divergent results Medeiros et al, 2006;Sample et al, 2006;Tafreshi et al, 2009).…”
Section: Other Perimetric Devicesmentioning
confidence: 99%